Comment le dieu biblique peut « aller au hasard » en hébreu mais pas en traduction - Atlan, Henri (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1995)
AbstractMedical doctor, biologist and professor in Paris and Jerusalem, the author has developed theories on the complexity and the self-organization of living organisms (Entre le cristal et la fumée, Seuil. 1979). Drawing on his profound knowledge of Jewish thought, the author has also studied the problems relating to bio-ethics as well as having analysed the existence of various fields of knowledge, thus confronting different models of rationality in their quest for truth (A tort et à raison. Seuil. 1986). In this article, he analyzes the polysemous nature and the philosophical implications of the concept of chance based on the translation of two verses in the hook of Leviticus, thus underscoring the hermeneutic virtues of translation, which are similar to those of scriptural commentary.